Factors That Influence Employee Engagement: A Study of Celestica Malaysia Sdn. Bhd. - Choo, Ling Suan (2009)
The purpose of this study is to examine and gain a better understanding of the drivers that influence the employee engagement in Celestica Malaysia Sdn. Bhd. This study was done among 97 exempt staffs in Celestica Malaysia Sdn. Bhd. Data were gathered through questionnaires and was being analyzed by using Statistical Package for Social Science (SPSS) version 16. Throughout the statistical analysis – correlation analysis, it is found that there is a significant relationship between the three independent variables namely Employee Communication, Rewards and Recognition and Employee Development with the dependent variables – Employee Engagement. Among all three independent variable,employee development is found to be the most independent variable in driving the employee engagement in Celestica.